Universal Jurisdiction: The Sierra Leone Profile - Bankole Thompson, Rosolu John (Springer, 2016)
The doctrine of universal jurisdiction has evolved throughout modern times in the context of global criminal justice as a paramount agent of combating impunity emanating from international criminality. Sierra Leone, as a member of the international community and the United Nations, has, in recent times, been a pioneer in the progressive application and development of international criminal law in the African region. Despite this role, the country’s profile, both in terms of the incorporation and application of the doctrine of universal jurisdiction, is deficient in several major respects falling far short of its dual international obligation not to provide safe havens from justice for perpetrators of international crimes and to combat impunity from such criminogenic acts. Hence, a compelling reason for the author to write this book was to provide a seminal scholarly work on the subject articulating the existing state of the law in Sierra Leone and highlighting the deficiencies in the law and factors inhibiting the exercise of universal jurisdiction in this UN member state. It was also to propose necessary substantive and procedural law reforms in the state’s jurisprudence on the subject.